3 - The Public Sphere in 21st Century Africa: Broadening the Horizons of Democratisation - Mustapha, Abdul Raufu (Africa Development, 2021)
The public sphere, as the crucible for public opinion, is indispensable to modern democratic politics. This paper traces the seminal contributions of the German critical theorist, Jurgen Habermas to the elaboration of the concept. However, while Habermas’ conception has had a profound impact, it has nevertheless been criticised on fundamental grounds. And contemporary globalisation and technological changes have also had important implications for our understanding of the concept. I seek to elaborate the development of the idea of the public sphere from Habermas to the era of internet globalisation. I also examine the specific ways the idea has found expression in post-colonial Africa, showing how the global intellectual trajectory shapes the applicability of the concept to specific African contexts. If the concept of the public sphere is to relate to African realities, it must be understood not as a single public – a la Habermas – or ‘Two Publics’ – a la Ekeh, but as a multiplicity of overlapping publics. I argue that we can fruitfully re-interpret contemporary democratisation in Africa against the backdrop of this understanding of the concept of the public sphere, taking full cognizance of the other criticisms of the concept.